2019
DOI: 10.1093/brain/awz044
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of the mesenchymal signature in brain tumours

Abstract: Although gliomas are thought to arise from a neural-glial lineage of ectodermal origin, many gliomas express a mesenchymal signature. Behnan et al. review the origins of this signature in glioma: it may arise via the tumour stroma, via NF1 -mutation in tumour cells and be influenced by the cell of origin, or arise in response to radiotherapy/chemotherapy/anti-angiogenic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
255
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(263 citation statements)
references
References 129 publications
(380 reference statements)
8
255
0
Order By: Relevance
“…In 2013, Bhat et al found that PN GSCs transformed to the MES state through the NF-κB pathway, with an elevated expression of CD44 and radioresistant phenotypes 37 . Thereafter, several studies were conducted to elucidate the potential mechanisms of how gliomas acquire the MES-signature through activating NF-κB transcriptional programs [38][39][40][41] . Furthermore, therapeutic approaches targeting the NF-κB pathway in GBM have (see figure on previous page) Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Bhat et al found that PN GSCs transformed to the MES state through the NF-κB pathway, with an elevated expression of CD44 and radioresistant phenotypes 37 . Thereafter, several studies were conducted to elucidate the potential mechanisms of how gliomas acquire the MES-signature through activating NF-κB transcriptional programs [38][39][40][41] . Furthermore, therapeutic approaches targeting the NF-κB pathway in GBM have (see figure on previous page) Fig.…”
Section: Discussionmentioning
confidence: 99%
“…103,104 CTCs have been found to be significantly associated with the prognosis of patients with brain cancer, with >5 times the CTC count noted among patients with progressive versus stable glioblastoma, and CTCs with a mesenchymal signature, a subtype correlated with tumor resistance to radiotherapy and chemotherapy, have been detected and reported to demonstrate promise for prognosis and treatment guidance. 105 CTCs also have been detected in cases of pituitary adenoma. 106 This type of tumor generally is considered to be benign, but disease recurrence is problematic because many patients are asymptomatic.…”
Section: Ctcs and Cns Cancersmentioning
confidence: 99%
“…CTCs have been detected for human glioblastoma, the most common and a highly aggressive and invasive brain cancer . CTCs have been found to be significantly associated with the prognosis of patients with brain cancer, with >5 times the CTC count noted among patients with progressive versus stable glioblastoma, and CTCs with a mesenchymal signature, a subtype correlated with tumor resistance to radiotherapy and chemotherapy, have been detected and reported to demonstrate promise for prognosis and treatment guidance …”
Section: Introductionmentioning
confidence: 99%
“…The role of EMT in non-epithelial tumours like malignant glioma is nonetheless uncertain. However, recent classification of mesenchymal subgroup of GBM strengthen the notion of glial-mesenchymal transition (GMT) similar to EMT-like process in glioma and may contribute to tumour progression, chemo-resistance and tumour relapse regardless of tumour grades (7). Several studies have investigated the expression of EMT markers such as vimentin, TWIST, SNAIL, E-cadherin and N-cadherin in malignant gliomas and demonstrated their apparent role in invasion, drug resistance and tumour recurrence (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%